(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Cross bite is a condition where one or more teeth may be abnormally malposed bucally or lingually or labially with reference to the opposing tooth or teeth. Different techniques have been used to correct cross bite. This paper concerns orthodontic management of different types of cross bite. Orthodontic treatment carried out with pre-adjusted (Roth type 018 slot) fixed brackets with space management and alignment to accomplish the treatment. The esthetics and occlusion were maintained after retention. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16162 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 34-37